Lithium metal battery

By using protective layer-enhanced current collectors and electrolytes of specific structures of organic solvents A and Compound C in lithium metal batteries, the thermal runaway and safety problems of lithium metal batteries when increasing capacity are solved, and higher cycling rate performance and safety performance are achieved.

CN119695235AActive Publication Date: 2025-03-25ZHUHAI COSMX BATTERY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411880594.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-25
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

While the existing lithium metal batteries increase the thickness of the negative electrode sheet active layer to expand capacity, they easily lead to an increase in lithium ion transmission distance, a decrease in ion conductivity, and intensified negative electrode expansion, resulting in thermal runaway and safety problems.

Method used

Using a current collector including a protective layer and an electrolyte containing an organic solvent A and Compound C of a specific structure, the tensile strength of the foil is increased through the protective layer, the expansion of the negative electrode active layer is inhibited, and the ion transport and flammability of the electrolyte are improved through the organic solvent A and Compound C, and the thermal safety performance of the battery is improved.

Benefits of technology

It effectively improves the thermal runaway problem of lithium metal batteries, improves the cycle rate and safety performance of the battery, and takes into account the improvement of battery capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005198110290000022
    Figure BDA0005198110290000022
  • Figure BDA0005198110290000023
    Figure BDA0005198110290000023
  • Figure BDA0005198110290000052
    Figure BDA0005198110290000052
Patent Text Reader

Abstract

The invention relates to the field of battery materials, and discloses a lithium metal battery. The invention provides a lithium metal battery. The lithium metal battery comprises a positive plate, a negative plate and electrolyte, the negative plate comprises at least one side surface of a current collector and an active layer arranged on the current collector, and the current collector comprises a foil and a protective layer arranged on at least one side surface of the foil; the thickness of the active layer is d [mu] m, and d is more than or equal to 30 and less than or equal to 100; the electrolyte comprises an organic solvent A and a compound C, the mass ratio of the organic solvent A in the electrolyte is a%, and a is more than or equal to 30 and less than or equal to 80. Through mutual cooperation of the organic solvent A, the protective layer and the compound C, the thermal runaway problem of the battery can be effectively improved, and the cycle rate capability of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery materials, and in particular to a lithium metal battery. Background Art

[0002] At present, in order to expand the capacity of lithium metal batteries, it is usually achieved by increasing the thickness of the active layer in the negative electrode sheet. However, when the thickness of the active layer in the negative electrode sheet is too thick, it will significantly increase the transmission distance of lithium ions in the electrode, reduce the ion conductivity, and intensify the expansion of the lithium metal negative electrode, increase side reactions, and then lead to heat generation and accumulation, which is prone to safety problems such as thermal runaway caused by overheating.

[0003] Regarding the safety issue of thermal runaway, relevant technical reports disclose that it can be improved by doping and coating the positive electrode material, reducing the thermal shrinkage rate of the diaphragm, increasing the thickness of the diaphragm or optimizing the electrolyte composition, thereby improving the safety performance of lithium metal batteries.

[0004] However, the above technical solutions disclosed so far cannot significantly improve the problem of thermal runaway while ensuring the battery capacity. Therefore, how to significantly improve thermal runaway and ensure safety while effectively increasing the battery capacity is a technical problem that those skilled in the art urgently need to solve. Summary of the invention

[0005] The present application provides a lithium metal battery, which aims to solve to a certain extent the problem that existing lithium metal batteries cannot take into account safety while ensuring the capacity of the battery.

[0006] The present application provides a lithium metal battery, including a positive electrode sheet, a negative electrode sheet and an electrolyte;

[0007] The negative electrode sheet comprises a current collector and an active layer disposed on at least one side of the current collector, and the current collector comprises a foil and a protective layer disposed on at least one side of the foil;

[0008] The thickness of the active layer is d μm, where d satisfies: 30≤d≤100;

[0009] The electrolyte includes an organic solvent A and a compound C, wherein the mass proportion of the organic solvent A in the electrolyte is a%, and a satisfies: 30≤a≤80;

[0010] The organic solvent A comprises at least one of the structures shown in Formula 1,

[0011] Formula 1: Wherein, R1, R2, and R3 are independently selected from H, halogen, halogen-substituted or unsubstituted hydrocarbon group and hydrocarbonoxy group having 1 to 8 carbon atoms, and R2 and R3 may also be connected to form a ring;

[0012] The compound C comprises at least one of the structures shown in Formula 2,

[0013] Formula 2: Wherein, R4 and R5 are independently selected from H, F substituted or unsubstituted hydrocarbon groups and hydrocarbonoxy groups having 1 to 10 carbon atoms.

[0014] In an optional embodiment, the organic solvent A comprises at least one of the following structural formulas 1-1 to 1-8:

[0015]

[0016] And / or, the compound C comprises at least one of the following structural formulas 2-1 to 2-8:

[0017]

[0018] And / or, the mass proportion of the compound C in the electrolyte is c%, and c satisfies: 0<c≤50.

[0019] In an optional embodiment, the electrolyte further includes a lithium salt B, and the lithium salt B includes at least one of lithium hexafluorophosphate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium bis(fluorosulfonylimide), lithium bis(trifluoromethylsulfonylimide), lithium difluorobis(oxalatophosphate), lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium hexafluoroantimonate, lithium hexafluoroarsenate, lithium bis(pentafluoroethylsulfonyl)imide, lithium tris(trifluoromethylsulfonyl)methyl lithium and lithium bis(trifluoromethylsulfonyl)imide;

[0020] Preferably, the mass proportion of lithium salt B in the electrolyte is b%, and b satisfies: 10≤b≤40.

[0021] In an optional embodiment, 0.4<d / (a+b)<1.7, preferably, 0.4<d / (a+b)<0.7.

[0022] In an optional embodiment, the surface capacity of the negative electrode sheet is x mAh / cm 2 , x satisfies: 5≤x≤12;

[0023] And / or, the tensile strength of the current collector is σMPa, σ satisfies: 350≤σ≤800;

[0024] And / or, the thickness of the protective layer is y nm, y satisfies: 0<y≤10; ay≥180, preferably, 650≥ay≥180, more preferably, 380≥ay≥280.

[0025] In an optional embodiment, the foil is a copper foil;

[0026] And / or, the material of the protective layer includes at least one of metal oxide, carbon-based material, and conductive polymer;

[0027] Preferably, the carbon-based material can be selected as at least one of graphite, soft carbon, hard carbon, and graphene, the conductive polymer can be selected as one or more of polyimide, polyaniline, polyacrylamide, and polypyrrole, and the metal oxide can be selected as one or more of Ni, Co, Cr, and Al oxides.

[0028] In an optional embodiment, the positive electrode sheet includes a positive electrode material, and the positive electrode material includes a ternary material;

[0029] Preferably, the specific surface area of ​​the ternary material is zm 2 / g, z satisfies: 0.4≤z≤2, preferably, 0.4≤z≤1.35.

[0030] In an optional embodiment, the electrolyte further includes a phosphorus-containing additive, and the amount of the phosphorus-containing additive added is f% of the mass of the electrolyte, where f satisfies: 0.1≤f≤5;

[0031] Furthermore, the phosphorus-containing additive includes one or more of lithium difluorophosphate, tri(2,2,2-trifluoroethyl) phosphate, triphenyl phosphate, ethoxypentafluorocyclotriphosphazene, triphenyl phosphine oxide, triphenyl phosphine, p-toluoyl phosphate, and toluene diphenyl phosphate.

[0032] In an optional embodiment, the electrolyte further includes a sulfur-containing additive, and the added amount of the sulfur-containing additive is e% of the mass of the electrolyte, and e satisfies: 0.1≤e≤3.

[0033] Furthermore, the sulfur-containing additive includes one or more of vinyl sulfate, 1,3-propane sultone, 1-propylene-1,3-sultone, 5-methylthiothiocyanate 2,2-dioxide, 1,3-propylene sultone, 2,4-butane sultone, 1,4-butane sultone, 1,3-butane sultone, and fluorinated 1,3-propane sultone.

[0034] The technical solution of this application has the following advantages:

[0035] The present application provides a lithium metal battery, including a negative electrode sheet with increased thickness of the active layer, a current collector with a protective layer, and an electrolyte containing an organic solvent A and a compound C. The protective layer in the present invention has the effect of increasing the tensile strength of the foil, can better avoid the problem of the foil breaking due to the increase of internal stress caused by the expansion of the active layer, and inhibits the expansion of the negative electrode active layer, and improves the thermal safety performance of the battery; the organic solvent A used in the present invention can effectively accelerate the transmission of ions, reduce the risk of thermal runaway, and at the same time, reduce polarization, reduce the expansion of the negative electrode sheet, and improve the safety performance of the battery; the compound C in the present invention can effectively reduce the flammability of the organic solvent A itself, and reduce the viscosity of the electrolyte, effectively improving the safety performance of the battery. The present invention can effectively improve the thermal runaway problem of the battery and improve the cycle rate performance of the battery by cooperating with the organic solvent A, the protective layer and the compound C.

[0036] Additional aspects and advantages of the embodiments of the present application will be described and shown in part in the subsequent description, or explained through the implementation of the embodiments of the present application. DETAILED DESCRIPTION

[0037] The following examples are provided for a better understanding of the present application, but are not limited to the best implementation mode described, and do not limit the content and protection scope of the present application. Any product identical or similar to the present application obtained by anyone under the inspiration of the present application or by combining the features of the present application with other prior arts shall fall within the protection scope of the present application.

[0038] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0039] In addition, the technical features involved in the different embodiments of the present application described below can be combined with each other as long as they do not conflict with each other.

[0040] The present application provides a lithium metal battery, including a positive electrode sheet, a negative electrode sheet and an electrolyte;

[0041] The negative electrode sheet comprises a current collector and an active layer disposed on at least one side of the current collector, and the current collector comprises a foil and a protective layer disposed on at least one side of the foil;

[0042] The thickness of the active layer in the negative electrode sheet is d μm, where d satisfies: 30≤d≤100, wherein the thickness d of the active layer refers to the thickness of the active layer on one side of the current collector;

[0043] The electrolyte includes an organic solvent A and a compound C, wherein the mass proportion of the organic solvent A in the electrolyte is a%, and a satisfies: 30≤a≤80;

[0044] The organic solvent A comprises at least one of the structures shown in Formula 1,

[0045] Formula 1: Wherein, R1, R2, and R3 are independently selected from H, halogen, halogen-substituted or unsubstituted hydrocarbon group and hydrocarbonoxy group having 1 to 8 carbon atoms, and R2 and R3 may also be connected to form a ring;

[0046] The compound C comprises at least one of the structures shown in Formula 2,

[0047] Formula 2: Wherein, R4 and R5 are independently selected from H, F substituted or unsubstituted hydrocarbon groups and hydrocarbonoxy groups having 1 to 10 carbon atoms.

[0048] The protective layer described in the present invention itself has a certain effect of increasing the tensile strength of the foil, can better avoid the problem of the foil breaking due to the increase of internal stress caused by the expansion of the thicker active layer, and alleviates the expansion of the negative electrode active layer to a certain extent; and the organic solvent A has higher chemical stability and lower viscosity than the traditional carbonate solvent, and the viscosity can be as low as <20mPa.s. The low viscosity can effectively ensure the good wettability between the organic solvent A and the electrode, and can better penetrate into the interior of the thicker lithium metal negative electrode, accelerate the transmission and desorption of ions, and thus improve the utilization rate of the active material, prevent the lithium metal negative electrode active layer from having too large a difference in lithium ion concentration between the surface and inner layers, reduce the polarization of the electrode, inhibit the expansion of the negative electrode, reduce side reactions, reduce heat generation and accumulation, and avoid the thermal runaway problem of the lithium metal battery; at the same time, the low viscosity is conducive to the rapid conduction of heat and reduces the safety hazards caused by heat concentration. However, the organic solvent A itself is flammable, so the battery in the present invention still has the risk of thermal runaway. In order to solve the above problem, the present invention adds the compound C to the organic solvent A. The compound C itself is not flammable and can improve the flammability of the electrolyte containing the organic solvent A. The compound C has a very low viscosity. Therefore, when the compound C is added to the electrolyte, it can not only improve the flammability of the electrolyte containing the organic solvent A, but also further reduce the viscosity of the electrolyte and improve the thermal safety performance of the battery. Therefore, the present invention can effectively improve the thermal runaway problem of the battery and improve the cycle rate performance of the battery by cooperating with the organic solvent A, the protective layer and the compound C.

[0049] As an example, the mass proportion a% of the organic solvent A in the electrolyte can be 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80% or in the range formed by any two of the above values; the thickness dμm of the active layer of the negative electrode sheet can be 30μm, 40μm, 50μm, 60μm, 70μm, 80μm, 90μm, 100μm or in the range formed by any two of the above values.

[0050] In an optional embodiment, the organic solvent A comprises at least one of the following structural formulas 1-1 to 1-8:

[0051]

[0052]

[0053] And / or, the compound C comprises at least one of the following structural formulas 2-1 to 2-8:

[0054]

[0055] In an optional embodiment, the mass proportion of the compound C in the electrolyte is c%, c satisfies: 0<c≤50, compound C does not dissolve the lithium salt B at all, does not participate in the electrochemical reaction at all, and does not affect the electrical performance; therefore, adding compound C to the electrolyte can improve the high performance of the battery fast charging without causing other side reactions.

[0056] As an example, the mass percentage of compound C in the electrolyte is c%, which can be 1%, 3%, 5%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50% or within the range of any two of the above values.

[0057] The electrolyte also includes lithium salt B. When organic solvent A is used as the main solvent of the electrolyte, since organic solvent A has good solubility for lithium salt, it can dissolve the higher content of lithium salt described in the present invention. In an optional embodiment, the mass proportion of lithium salt B in the electrolyte is b%, and b satisfies: 10≤b≤40; preferably 20≤b≤40; under this condition, the content of movable lithium ions per unit volume is high, which can increase the ionic conductivity in the negative electrode sheet and effectively improve the high performance of battery fast charging.

[0058] As an example, the mass proportion b% of the lithium salt B in the electrolyte can be 10%, 15%, 20%, 25%, 30%, 35%, 40% or within a range formed by any two of the above values.

[0059] In an optional embodiment, the lithium salt B includes at least one of lithium hexafluorophosphate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium difluorobis(oxalatophosphate), lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium hexafluoroantimonate, lithium hexafluoroarsenate, lithium bis(pentafluoroethylsulfonyl)imide, lithium tris(trifluoromethylsulfonyl)methyllithium and lithium bis(trifluoromethylsulfonyl)imide.

[0060] In an optional embodiment, by comprehensively regulating the mass proportion a% of the organic solvent A in the electrolyte, the mass proportion b% of the lithium salt B in the electrolyte, and the thickness dμm of the active layer of the negative electrode sheet, and by controlling a, b, and d within the range of a specific relationship, that is, controlling 0.4<d / (a+b)<1.7, the cycle performance and safety of the battery can be effectively taken into account; more preferably, within the range of 0.4<d / (a+b)<0.7, better cycle performance and safety performance can be effectively achieved.

[0061] As an example, d / (a+b) may be 0.4, 0.7, 0.9, 1.1, 1.3, 1.5, 1.7, or a range between any two of the above values.

[0062] In an optional embodiment, when the negative electrode material has a larger surface capacity, the battery can have a higher energy density, which can meet people's demand for high energy density and large discharge current; however, too large a surface capacity also means that the negative electrode volume expansion is larger and the lithium dendrite growth is more serious during the charge and discharge process. Therefore, the surface capacity of the negative electrode sheet in the present invention is x mAh / cm 2 , x satisfies: 5≤x≤12.

[0063] As an example, the surface capacity of the negative electrode is x mAh / cm 2 It can be 5mAh / cm 2 、6mAh / cm 2 、7mAh / cm 2 、8mAh / cm 2 、9mAh / cm 2 、10mAh / cm 2 、11mAh / cm 2 、12mAh / cm 2 Or within the range formed by any two of the above values.

[0064] In the present invention, when the negative electrode material has a larger surface capacity, it also means that the negative electrode volume expansion is greater and the lithium dendrite growth is more serious during the charge and discharge process. The present invention adopts the current collector with greater tensile strength than ordinary current collectors to avoid breakage due to excessive stress; at the same time, through the protective film with a specific thickness on the surface of the current collector, based on its certain buffering effect, it provides stress buffering during the lithium metal deposition and stripping process, and cooperates with the current collector to reduce cracks and breakage caused by volume changes.

[0065] In an optional embodiment, the tensile strength of the current collector is σMPa; when the current collector of the present invention has a greater tensile strength than that of an ordinary current collector, it can prevent the current collector from breaking due to excessive stress. However, since the current collector wants to obtain a greater tensile strength, its thickness needs to be thicker, which is not conducive to maintaining a higher energy density. The tensile strength of the current collector in the present invention is preferably such that σ satisfies: 350≤σ≤800.

[0066] As an example, the tensile strength σ MPa of the current collector may be 350 MPa, 400 MPa, 450 MPa, 500 MPa, 550 MPa, 600 MPa, 650 MPa, 700 MPa, 750 MPa, 800 MPa, or within a range formed by any two of the above values.

[0067] In an optional embodiment, the thickness of the protective layer is y nm; the protective film on the surface of the foil (current collector) has a certain buffering effect, providing stress buffering during the lithium metal deposition and stripping process, reducing cracks and fractures caused by volume changes, but when the protective thickness is too large, it will lead to a decrease in the energy density per unit volume of the battery. Therefore, in the present invention, preferably, y satisfies: 0<y≤10.

[0068] As an example, the thickness y nm of the protective layer may be 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, or a range formed by any two of the above values.

[0069] In an optional embodiment, by comprehensively controlling the product value of the mass proportion a% of the organic solvent A in the electrolyte and the thickness y nm of the protective layer, the battery energy density can be improved and a relatively high cycle performance can be effectively obtained while ensuring safety performance. Specifically, when the a% content is low, the thickness of the protective layer needs to be increased to ensure safety performance; while when the a% content is high, the expansion of the negative electrode is relatively reduced, the internal stress is reduced, the viscosity of the electrolyte is reduced, and the wettability to the negative electrode is improved. Under the condition of ensuring safety performance, the thickness of the protective layer can be reduced, thereby reducing the battery volume, thereby increasing the energy density per unit volume of the battery and improving the cycle performance. Therefore, ay≥180, preferably, 650≥ay≥180, more preferably, 380≥ay≥280.

[0070] Those skilled in the art will understand that the surface capacity in this application refers to the number of lithium ions or electricity that can be accommodated per square centimeter of negative electrode area. Calculation of surface capacity: Surface capacity = Capacity (mAh) / Negative electrode area. Capacity testing is performed by assembling batteries and testing the battery charging capacity.

[0071] The tensile strength test method is as follows: the current collector is cut into small strips of 15 mm ± 0.2 mm, and the two ends of the current collector are clamped in the clamps respectively using a WD-D3 electronic universal testing machine with a gap of 50 mm between the upper and lower clamps. The test is started at a speed of 100 mm / min until the equipment stops testing, and the breaking strength (tensile strength) σ is recorded; the error does not exceed 10% after three tests, and the average value is taken;

[0072] Alternatively, the negative electrode sheet is cut into small strips of 15 mm ± 0.2 mm, and then the active material on the surface is gently wiped off with alcohol. After natural air drying, the negative electrode sheet is tested using a WD-D3 electronic universal testing machine using the above-mentioned testing method.

[0073] In an optional embodiment, the foil is a copper foil;

[0074] And / or, the material of the protective layer is at least one of an ion conductor, a conductive polymer, and a metal oxide; preferably, the material of the protective layer includes at least one of Cr2O3, Al2O3, Co3O4, NiO, graphite, polyimide, polyaniline, polyacrylamide, and polypyrrole.

[0075] In an optional embodiment, the positive electrode material in the positive electrode sheet is NCM ternary material;

[0076] Preferably, the specific surface area of ​​the NCM ternary material is zm 2 / g, z satisfies: 0.4≤z≤2, preferably, 0.4≤z≤1.35.

[0077] The larger the specific surface area in the NCM ternary positive electrode material, the more surface active sites it has, which helps to improve the wettability of the electrolyte on the surface of the positive electrode material, thereby promoting the penetration of the electrolyte and the transmission of lithium ions, and thus can better match the thicker negative electrode material described in the present invention, so that the battery has better fast charging performance. However, if the specific surface area is too large, the ion transmission rate may be limited, resulting in changes in the electrode potential, affecting the performance of the battery. At the same time, the mechanical strength is low, and it is easy to break or deform when subjected to external force, and the surface may change during the cycle, affecting the cycle stability. In the present invention, the specific surface area z of the NCM ternary material is set to 0.4-2, preferably 0.4-1.35.

[0078] As an example, the specific surface area zm of NCM ternary materials 2 / g can be 0.4m 2 / g, 0.5m 2 / g, 0.6m 2 / g, 0.7m 2 / g, 0.8m 2 / g, 0.9m 2 / g, 1.0m 2 / g, 1.1m 2 / g, 1.2m 2 / g, 1.3m 2 / g, 1.4m 2 / g, 1.5m 2 / g, 1.7m 2 / g, 2.0m 2 / g or within the range formed by any two of the above values.

[0079] In an optional embodiment, the electrolyte further includes a phosphorus-containing additive, and the amount of the phosphorus-containing additive added is f% of the mass of the electrolyte, where f satisfies: 0≤f≤5.

[0080] Since the melting point of the compound A of the present invention is higher than that of ordinary carbonate solvents, it may change state at low temperature, forming a solid, resulting in the precipitation of lithium salts, thereby affecting the low-temperature cycle performance; in addition, the negative electrode sheet of the present invention is thicker than that of ordinary lithium metal batteries, so at low temperatures, the low-temperature cycle problem of the lithium metal battery of the present invention is more significant. The phosphorus-containing additive of the present invention can not only form a stable CEI film on the surface of the positive electrode, protecting the structural stability of the positive electrode material, but its decomposition product can also participate in the solvation structure, reduce the migration resistance of lithium ions in the electrolyte, and improve its conductivity.

[0081] As an example, the addition amount f% of the phosphorus-containing additive can be 0.1%, 0.3%, 0.5%, 0.7%, 0.9%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% or within the range of any two of the above values.

[0082] Preferably, the phosphorus-containing additive includes one or more of lithium difluorophosphate, tri(2,2,2-trifluoroethyl) phosphate, triphenyl phosphate, ethoxypentafluorocyclotriphosphazene, triphenyl phosphine oxide, triphenyl phosphine, p-toluoyl phosphate, and toluene diphenyl phosphate.

[0083] In an optional embodiment, the electrolyte further includes a sulfur-containing additive, and the added amount of the sulfur-containing additive is e% of the mass of the electrolyte, where e satisfies: 0≤e≤3.

[0084] In the present invention, sulfur compounds can also be included in the electrolyte. The sulfur-containing compounds can form a low-impedance SEI film on the surface of the negative electrode, reduce the interface impedance, thereby improving the contact and electron transmission performance of the electrode / electrolyte interface, reducing polarization, improving the power performance of the battery, and reducing the risk of thermal runaway.

[0085] As an example, the addition amount e% of the sulfur-containing additive can be 0.1%, 0.3%, 0.5%, 0.7%, 0.9%, 1.5%, 2%, 2.5%, 3% or a range formed by any two of the above values.

[0086] Preferably, the sulfur-containing additive includes one or more of vinyl sulfate, 1,3-propane sultone, 1-propylene-1,3-sultone, 5-methylthiothiocyanate 2,2-dioxide, 1,3-propylene sultone, 2,4-butane sultone, 1,4-butane sultone, 1,3-butane sultone, and fluorinated 1,3-propane sultone.

[0087] More preferably, 0<f+e≤6, the phosphorus-containing additive and the sulfur-containing additive of the present invention improve the low-temperature cycle performance of the battery from the aspects of electrolyte and interface impedance respectively, and the low-temperature cycle performance of the battery is significantly improved by comprehensively controlling the content of the phosphorus-containing additive and the sulfur-containing additive.

[0088] The positive electrode sheet of the present invention comprises a current collector and a positive electrode active material layer arranged on the surface of the current collector, the positive electrode active material layer comprises 80% to 99.8% of a ternary material, 0.1% to 10% of a conductive agent, and 0.1% to 10% of a binder; preferably, the positive electrode active material layer comprises 90% to 99.6% of a high-nickel ternary material, 0.2% to 5% of a conductive agent, and 0.2% to 5% of a binder.

[0089] The present invention does not particularly limit the conductive agent in the positive electrode sheet, which can be selected from the conductive agents commonly used in the art, including but not limited to one or more of acetylene black, conductive carbon black, Ketjen black, conductive graphite, carbon nanotubes, conductive carbon fibers, and graphene;

[0090] The present invention does not particularly limit the binder in the positive electrode sheet, which can be selected from binders conventionally used in the art, including but not limited to one or more of polyvinylidene fluoride, polytetrafluoroethylene, sodium carboxymethyl cellulose, styrene-butadiene rubber, and polyethylene oxide.

[0091] The negative electrode sheet of the present invention comprises a current collector and an active layer disposed on at least one side of the current collector, the active layer comprises a negative electrode active material, the negative electrode active material can be a negative electrode active material for lithium metal batteries known in the art, the negative electrode active material can be selected from at least one of lithium metal and lithium alloy, the current collector of the negative electrode sheet comprises a foil and a protective layer disposed on at least one side of the foil, the foil can be selected from high-strength copper foil in the art. The active layer also comprises a conductive agent and a binder, the present invention does not specifically limit the types of conductive agents and binders in the negative electrode sheet, the selection range can refer to the types of conductive agents and binders in the positive electrode sheet, and will not be repeated here.

[0092] The material and shape of the separator used in the lithium metal battery of the present application are not particularly limited, and may include any technology disclosed in the prior art.

[0093] The present application is further described in detail below in conjunction with specific examples, which should not be construed as limiting the scope of protection claimed in the present application. In all examples and comparative examples of the present application, the unit wt% represents the mass percentage content.

[0094] Example 1

[0095] A lithium metal battery, the preparation process of which is as follows:

[0096] (1) Preparation of positive electrode sheet

[0097] The specific surface area z is 1m 2 / g of positive electrode active material (NCM811), polyvinylidene fluoride, conductive carbon black and carbon nanotubes are mixed in a mass ratio of 96:2:1.5:0.5, N-methylpyrrolidone (NMP) is added, and the mixture is stirred under the action of a vacuum stirrer until the mixed system becomes a positive electrode active slurry with uniform fluidity; the positive electrode active slurry is evenly coated on both surfaces of an aluminum foil; the coated aluminum foil is dried, and the desired positive electrode sheet is obtained by rolling and slitting, wherein the surface density of the positive electrode sheet is 3.5 mAh / cm 2 .

[0098] (2) Preparation of negative electrode sheet

[0099] By means of physical roller pressing, lithium metal is compounded onto a copper foil with a surface protective layer y of 5 nm and a tensile strength σ of 500 MPa. The protective layer material is Cr2O3. The pressure of the roller is adjusted to coat the copper foil with lithium alloy on both sides. The thickness of the active layer in the negative electrode sheet is d μm. After cutting and slitting, the negative electrode sheet is obtained and placed in a dry argon atmosphere glove box for storage. The surface capacity x of the negative electrode sheet is 7 mAh / cm 2 .

[0100] (3) Preparation of electrolyte

[0101] In a glove box filled with argon (H2O<0.1ppm, O2<0.1ppm), b% of lithium salt based on the total mass of the electrolyte was added to compound A based on a% of the total mass of the electrolyte, dissolved and stirred evenly, c% of compound C based on the total weight of the electrolyte was added, and then 1.5% of lithium difluorophosphate and 1% of vinyl sulfate based on the total mass of the electrolyte were added, and the electrolyte was obtained after stirring evenly. The specific addition amounts are shown in Table 1.

[0102] (4) Preparation of batteries

[0103] The positive electrode sheet prepared in step (1), the negative electrode sheet prepared in step (2) and the separator are stacked in the order of positive electrode sheet, separator, negative electrode sheet and separator to obtain a battery cell; the battery cell is placed in an outer packaging aluminum foil, the electrolyte prepared in step (3) is injected into the outer packaging aluminum foil, and a lithium metal battery is obtained through vacuum packaging, standing, forming, shaping, sorting and other processes.

[0104] Table 1

[0105]

[0106]

[0107] The battery of the present invention has a charge and discharge range of 3.0-4.25V.

[0108] Comparative Example 1

[0109] A lithium metal battery, which differs from Example 1-1 in that the thickness dμm of the active layer of the negative electrode sheet is adjusted to 120μm, and other parameter conditions not shown are exactly the same as those of Example 1-1.

[0110] Comparative Example 2

[0111] A lithium metal battery, which is different from Example 1-1 in that the content of compound C is 0%, and the content of compound A is adjusted to 76.5% simultaneously, and other parameter conditions not shown are exactly the same as those of Example 1-1.

[0112] Comparative Example 3

[0113] A lithium metal battery, which is different from Example 1-1 in that there is no protective layer on the surface of the foil, that is, the thickness of the protective layer is 0 nm, and other parameter conditions not shown are exactly the same as those of Example 1-1.

[0114] Comparative Example 4

[0115] A lithium metal battery, which differs from Example 1-1 in that ethylene carbonate (EC) is used to replace compound A, and the EC content is 65%. Other parameter conditions not shown are exactly the same as those of Example 1-1.

[0116] Example 2

[0117] A lithium metal battery, which is different from Example 1-1 in that the parameter specifications of the negative electrode sheet and the positive electrode sheet are set differently, and the specific settings are shown in Table 2 below:

[0118] Table 2

[0119]

[0120]

[0121] Other parameter conditions not shown are exactly the same as those in Example 1-1.

[0122] Example 3

[0123] A lithium metal battery, which differs from Example 1-1 in that the amount and type of the sulfur-containing additive and the phosphorus-containing additive are different, and the content of the compound A is adjusted accordingly, and the specific settings are shown in Table 3 below:

[0124] Table 3

[0125] a b c e f d Sulfur-containing additives Phosphorus-containing additives Example 3-1 66 21 11.5 0 1.5 55 Vinyl Sulfate Lithium difluorophosphate Example 3-2 66 21 11.5 0.1 1.4 55 Vinyl Sulfate Lithium difluorophosphate Example 3-3 63 21 11.5 3 1.5 55 Vinyl Sulfate Lithium difluorophosphate Embodiment 3-4 61 21 11.5 5 1.5 55 Vinyl Sulfate Lithium difluorophosphate Embodiment 3-5 65 21 11.5 1 1.5 55 1,3-Propene sultone Lithium difluorophosphate Embodiment 3-6 65 21 11.5 1 1.5 55 5-Methyloxathiolane 2,2-dioxide Lithium difluorophosphate Embodiment 3-7 66.5 21 11.5 1 0 55 Vinyl Sulfate Lithium difluorophosphate Embodiment 3-8 66.5 21 11.5 0.9 0.1 55 Vinyl Sulfate Lithium difluorophosphate Embodiment 3-9 63.5 21 11.5 1 3 55 Vinyl Sulfate Lithium difluorophosphate Embodiment 3-10 61.5 21 11.5 1 5 55 Vinyl Sulfate Lithium difluorophosphate Example 3-11 60.5 21 11.5 1 6 55 Vinyl Sulfate Lithium difluorophosphate Example 3-12 65 21 11.5 1 1.5 55 Vinyl Sulfate Triphenyl phosphate Example 3-13 65 21 11.5 1 1.5 55 Vinyl Sulfate Ethoxypentafluorocyclotriphosphazene

[0126] Other parameter conditions not shown are exactly the same as those in Example 1-1.

[0127] Experimental example

[0128] The lithium ion batteries obtained in the examples and comparative examples were subjected to cycle performance tests and short circuit safety tests, respectively.

[0129] 1. 0℃0.2C / 1C cycle performance test

[0130] The battery obtained in the embodiment and the comparative example was discharged at 0°C with a current of 1C to 3.0V, then charged at a constant current of 0.2C to a voltage of 4.25V, then charged at a constant voltage at 4.25V to a current of 0.05C, left to stand for 5 minutes, and then discharged at a constant current of 1C to a voltage of 3.0V. This is one charge and discharge cycle. The battery thickness was recorded, and the discharge capacity of the first week of the test was counted as x mAh, and the discharge capacity of the Nth week was counted as y mAh; the capacity of the Nth week was divided by the capacity of the first week to obtain the cycle capacity retention rate R=y / x of the Nth week, and the number of cycles when the battery capacity retention rate was 80% was recorded.

[0131] 2. 25℃ 0.2C / 1C cycle performance test

[0132] The battery obtained in the embodiment and the comparative example was discharged at 25°C at a current of 1C to 3.0V, then charged at a constant current of 0.2C to a voltage of 4.25V, then charged at a constant voltage at 4.25V to a current of 0.05C, left to stand for 5 minutes, and then discharged at a constant current of 1C to a voltage of 3.0V. This is a charge and discharge cycle. The battery thickness was recorded, and the discharge capacity of the first week of the test was calculated as xmAh, and the discharge capacity of the Nth week was calculated as ymAh; the capacity of the Nth week was divided by the capacity of the first week to obtain the cycle capacity retention rate of the Nth week R=y / x, and the number of cycles when the battery capacity retention rate was 80% was recorded.

[0133] 3. 25℃ 0.5C / 3C cycle test

[0134] The battery obtained in the embodiment and the comparative example was discharged at 25°C at a current of 3C to 3.0V. Then it was charged at a constant current of 0.5C to a voltage of 4.25V, and then charged at a constant voltage at 4.25V to a current of 0.05C, left to stand for 5 minutes, and then discharged at a constant current of 3C to a voltage of 3.0V. This is a charge and discharge cycle. The discharge capacity of the first week of the test is x mAh, and the discharge capacity of the Nth week is y mAh; the capacity of the Nth week is divided by the capacity of the first week to obtain the cycle capacity retention rate R=y / x of the Nth week, and the number of cycles when the battery capacity retention rate is 80% is recorded.

[0135] 4. Battery short circuit safety test

[0136] The batteries obtained in the examples and comparative examples were discharged at 25°C at a current of 5C to 3.0V. Then they were charged at a constant current of 1C to a voltage of 4.25V, and then charged at a constant voltage of 4.25V to a current of 0.05C, left to stand for 5 minutes, and then discharged at a constant current of 5C to a voltage of 3.0V. This was a charge and discharge cycle. During the cycle, if the voltage value suddenly dropped, especially from a normal value to a level close to zero, it indicated that a short circuit occurred inside the battery. Record whether the battery had thermal runaway, fire or explosion when the battery was short-circuited.

[0137] The above test results of the embodiments of the present invention and the comparative examples are shown in Tables 4-6.

[0138] Table 4

[0139]

[0140]

[0141] Table 5

[0142]

[0143] Table 6

[0144]

[0145] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection created by this application.

Claims

1. A lithium metal battery, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, characterized in that: The negative electrode sheet comprises a current collector and an active layer disposed on at least one side of the current collector, and the current collector comprises a foil and a protective layer disposed on at least one side of the foil; The thickness of the active layer is d μm, where d satisfies: 30≤d≤100; The electrolyte includes an organic solvent A and a compound C, wherein the mass proportion of the organic solvent A in the electrolyte is a%, and a satisfies: 30≤a≤80; The organic solvent A comprises at least one of the structures shown in Formula 1, Formula 1: Wherein, R1, R2, and R3 are independently selected from H, halogen, halogen-substituted or unsubstituted hydrocarbon group and hydrocarbonoxy group having 1 to 8 carbon atoms, and R2 and R3 may also be connected to form a ring; The compound C comprises at least one of the structures shown in Formula 2, Formula 2: Wherein, R4 and R5 are independently selected from H, F substituted or unsubstituted hydrocarbon groups and hydrocarbonoxy groups having 1 to 10 carbon atoms.

2. The lithium metal battery according to claim 1, characterized in that The organic solvent A comprises at least one of the following structural formulas 1-1 to 1-8: And / or, the compound C comprises at least one of the following structural formulas 2-1 to 2-8: And / or, the mass proportion of the compound C in the electrolyte is c%, and c satisfies: 0<c≤50.

3. The lithium metal battery according to claim 1 or 2, characterized in that: The electrolyte also includes a lithium salt B, wherein the lithium salt B includes at least one of lithium hexafluorophosphate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium difluorobis(oxalatophosphate), lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium hexafluoroantimonate, lithium hexafluoroarsenate, lithium bis(pentafluoroethylsulfonyl)imide, lithium tris(trifluoromethylsulfonyl)methyl lithium and lithium bis(trifluoromethylsulfonyl)imide; Preferably, the mass proportion of lithium salt B in the electrolyte is b%, and b satisfies: 10≤b≤40.

4. The lithium metal battery according to claim 3, characterized in that The lithium metal battery satisfies: 0.4<d / (a+b)<1.7; preferably, 0.4<d / (a+b)<0.

7.

5. The lithium metal battery according to any one of claims 1 to 4, characterized in that: The surface capacity of the negative electrode sheet is x mAh / cm 2 , x satisfies: 5≤x≤12; And / or, the tensile strength of the current collector is σMPa, σ satisfies: 350≤σ≤800; And / or, the thickness of the protective layer is y nm, y satisfies: 0<y≤10; ay≥180, preferably, 650≥ay≥180, more preferably, 380≥ay≥280.

6. The lithium metal battery according to any one of claims 1 to 4, characterized in that: The foil is copper foil; And / or, the material of the protective layer includes at least one of metal oxide, carbon-based material, and conductive polymer; Preferably, the material of the protective layer includes at least one of Cr2O3, Al2O3, Co3O4, NiO, graphite, polyimide, polyaniline, polyacrylamide and polypyrrole.

7. The lithium metal battery according to any one of claims 1 to 6, characterized in that: The positive electrode sheet includes a positive electrode material, and the positive electrode material includes a ternary material; Preferably, the specific surface area of ​​the ternary material is zm 2 / g, z satisfies: 0.4≤z≤2, preferably, 0.4≤z≤1.

35.

8. The lithium metal battery according to any one of claims 1 to 7, characterized in that: The electrolyte also includes a phosphorus-containing additive and / or a sulfur-containing additive.

9. The lithium metal battery according to claim 8, characterized in that The amount of the phosphorus-containing additive added is f% of the mass of the electrolyte, where f satisfies: 0.1≤f≤5; And / or, the added amount of the sulfur-containing additive is e% of the mass of the electrolyte, and e satisfies: 0.1≤e≤3.

10. The lithium metal battery according to claim 8, characterized in that The phosphorus-containing additive includes one or more of lithium difluorophosphate, tris(2,2,2-trifluoroethyl) phosphate, triphenyl phosphate, ethoxy pentafluorocyclotriphosphazene, triphenyl phosphine oxide, triphenyl phosphine, p-toluoyl phosphate, and toluene diphenyl phosphate; And / or, the sulfur-containing additive includes one or more of vinyl sulfate, 1,3-propane sultone, 1-propylene-1,3-sultone, 5-methylthiothiocyanate 2,2-dioxide, 1,3-propylene sultone, 2,4-butane sultone, 1,4-butane sultone, 1,3-butane sultone, and fluorinated 1,3-propane sultone.

Citation Information

Patent Citations

  • Lithium ion secondary battery

    CN110943215A

  • Negative plate and lithium ion battery

    CN112786832A

  • Secondary battery and electronic device

    CN117199392A

  • Electrolyte, lithium ion battery and electric device

    CN117954694A

  • Lithium-ion secondary battery

    WO2020237713A1